PERTANGGUNGJAWABAN PELAKU TINDAK PIDANA PEMBUNUHAN BERENCANA YANG DILAKUKAN OLEH ANAK (Studi Putusan Pengadilan Negeri Nomor 16/Pid.Sus-Anak/2016/PN.Cbn) - Djesi Ariani (Universitas Islam Sumatera Utara, 2020)
AbstractChildren are a mandate from God Almighty which is inherent in their dignity as a whole human being. Every child has dignity and value that is worthy of high regard and every child born must have his/her rights without the child's request. The problems in this thesis are: the responsibility of children as perpetrators in criminal acts of premeditated murder in the Indonesian legal system, legal protection against children as perpetrators of criminal offenses planned in District Court Decision Number 16 / Pid.Sus-Anak / 2016 / PN.Cbn , the legal considerations of the judges against children as perpetrators of premeditated murder in District Court Decision Number 16 / Pid.Sus-Anak / 2016 / PN.Cbn.Legal Protection of Children in Criminal Acts Based on Law Number 11 Year 2012, from the results of the study, it is stated that children who are dealing with the law, including children as victims or children as perpetrators of crime, it is appropriate for children who are in conflict with the law to get legal protection both as the perpetrators or as the victims.Keywords: Criminal Liability, Planned Murder, Children